BIOLOGY AND MORPHOMETRIC OF DIFFERENT LIFE STAGES OF THE ORIENTAL FRUIT FLY (BACTROCERA DORSALIS HENDLE) (DIPTERA: TEPHRITIDAE) ON THREE VARIETIES OF MANGO OF SINDH, PAKISTAN - A. Amur; N. Memon; M. A. Shah; A. Ansari; D. A. Solangi; B. Mal (Journal of Animal and Plant Sciences, 2017)
A study on the biology and morphometric of different life stages of Bactrocera dorsalis (Hendle) was carried out on three varieties of mango, namely Beganpali, Sindhri and Chunsa in laboratory under controlled conditions 26±1ᵒc and 65±5%, at the department of Zoology University of Sindh Jamshoro, from June to August 2013. It was observed that the eggs of Bactrocera dorsalis were white, shiny, rice shaped, slightly curved, elongated and tapered at the anterior end; whereas the posterior end is broadly rounded. The average length and width were 0.54±0.11mm and 0.19±0.08mm, respectively. The first and second instars measured 2.6±0.75mm and 0.55± 5.88mm in length respectively, and 0.27±0.82mm and 2.34±0.7mm in width respectively. The 3rd instar was very active, jumping from mango fruits to sand measured 7.69±0.72mm in length and 3.58±0.25mm in width. The puparia measured 4.47±0.64mm in length and 2.69±0.16 mm in width. The duration of egg hatching and the larval, pre-pupal and pupal period was 1.61±0.51days, and 9.97±2.25 days, 2.07±0.86 days and 8.52±0.88 days respectively. The average pre-oviposition period was 13.55±1.33, whereas the oviposition period was 21.46±1.42 days. Fecundity varied from 14-15 eggs per day.  Sex ratio (♂: ♀) was 1:3. When adult fed on different diets such as on mango (natural diet) longevity extended from 20-30 days to males and 25-45 days for females, and when fed on water only 4-5 days male and female 5-8, while when they were fed both on (sugar and water) 13-25 days male and 15-30 days female, but without food the longevity was survived to only for 1-2 days. The longevity of fruit flies on different diets was significantly different (P<0.05). Developmental time duration of life stages of Bactrocera dorsalis was recordedon Chunsa, Sindhri, Beganpali varieties, incubation of egg (1.5±0.02 days, 2.3±0.16 days, 2.39±0.01 days, respectively), Larval developmental period (6.51±0.2 days, 7.5±0.16 days, 7.4±0.16 days, respectively), Pupal period (8.8±0.46 days, 8.9±0.40 days, 8.5±0.16 days, respectively), total life cycle period (16.8±0.086 days, 18.72±0.72, 18.29±0.33 days, respectively), There were no significant difference (P>0.05) between the developmental time of life stages of  Bactrocera dorsalis  on three varieties of mango .
Keywords: Biology; Morphometric; Oriental fruit fly; Mango varieties